Metaphors in Guardian Online and Mail Online Opinion-page Content on Climate Change: War, Religion, and Politics. Issue 4 (4th July 2017) - Atanasova, Dimitrinka; Koteyko, Nelya
Abstract : In climate change-related media discourses metaphors are used to (re-)conceptualize climate change science as well as climate change mitigation/adaptation efforts. Using critical metaphor analysis, we study linguistic and conceptual metaphors in opinion-page content from the British online newspapers Guardian Online and Mail Online, while paying attention to the arguments they advance. We find that Guardian Online employed war metaphors to advance pro-climate change arguments. War metaphors were used to (1) communicate the urgency to act on climate change and (2) conceptualize climate change politics. Mail Online employed religion metaphors to furnish skeptic/contrarian arguments. Religion metaphors were used to (1) downplay the urgency to act on climate change and (2) conceptualize transitions from climate change belief to skepticism. These findings raise concerns about sustained policy gridlock and refute expectations about novelty in climate change-related media discourses (as both war and religion have a history of use).